Interstate air pollution governance in the United States: Exploring Clean Air Act Section 126 - Underwood, Alixandra; Marcantonio, Richard; Wood, Danielle; Crippa, Paola (Springer, 2024)
Air pollution is arguably the most pressing human health concern today, accounting for approximately 7–9 million premature deaths worldwide. In the United States, more than 40% of early deaths caused by air pollution are assessed to be caused by emissions produced by neighboring states. This article examines one of the governance mechanisms used by the U.S. to address this issue: section 126 of the Clean Air Act. Critical factors including case length, evidence used, and case outcome are compiled for the population of section 126 petitions submitted from 2000–2022. This evidence is assessed using comparative case analysis. The findings reinforce two issues with the petition process already identified in the literature–the use of cost as a proxy for significance and the excessive and unclear burden of proof placed on downwind states–adding texture to the latter issue by examining the modeling techniques used by downwind states. This analysis identifies lengthy response timelines as an additional issue and calls to attention the infrequency with which the EPA has formally accepted petitions. Collectively, these issues increase the cost, complexity, and unpredictability of filing a section 126 petition.